2017
DOI: 10.1159/000477906
|View full text |Cite
|
Sign up to set email alerts
|

Stress Measured by Allostatic Load in Neurologically Impaired Children: The Importance of Nutritional Status

Abstract: Background: Allostatic load (AL) is the cumulative physiological wear and tear that results from repeated efforts to adapt to stressors over time. The life stress response is modified by nutritional status. Aim: We estimated AL scores among neurologically impaired (NI) children; the association with malnutrition was also evaluated. Methods: Forty-one patients with severe disabilities were included. Data based on 15 biomarkers were used to create the AL score. A dichotomous outcome of high AL was defined for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…As such, our preliminary analyses evaluated the potential contributions of energy intake (kcal) and physical activity to our main outcome in response to previously published data supporting associations of these parameters with body composition and with stress response. 3,9 However, when energy-intake variables and physical activity variables (obtained from 24-h dietary recalls and questionnaires, respectively, as described elsewhere 24 ) were added as covariates in the models no statistical contributions were observed from these measures (data not shown). Consequently, these variables were not included in our statistical models.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As such, our preliminary analyses evaluated the potential contributions of energy intake (kcal) and physical activity to our main outcome in response to previously published data supporting associations of these parameters with body composition and with stress response. 3,9 However, when energy-intake variables and physical activity variables (obtained from 24-h dietary recalls and questionnaires, respectively, as described elsewhere 24 ) were added as covariates in the models no statistical contributions were observed from these measures (data not shown). Consequently, these variables were not included in our statistical models.…”
Section: Discussionmentioning
confidence: 97%
“…The use of ALoad as measure of chronic stress and its association with health outcomes has been highly described in the literature. 6,[8][9][10]18,19 While there are variations in how ALoad is calculated, it has been suggested that ALoad calculations in adults should include biomarkers from three systems (cardiovascular, metabolic, and immune/ inflammatory). 7 In children, to measure the association with paediatric obesity, ALoad index typically includes markers such as homeostasis model assessment-insulin resistance (HOMA-IR), total cholesterol, triglycerides, blood pressure (systolic and diastolic), C-reactive protein (CRP), and others.…”
Section: Allostatic Load Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In individuals exposed to repeated or chronic stress, such as disability, the glucocorticoid (GC)-dependent stress-response negative feedback mechanism is impaired, leading to GC receptor resistance, and high systemic levels of molecular stress mediators, affecting the immune system and damaging multiple organs and tissues over time (13). A high cumulative physiological wear and tear, referred to allostatic load (AL) and considered a marker of chronic stress, has already been described in disabled children (14). AL is a preclinical marker of pathophysiological processes that can be considered a key mediator of adversity and negative health outcomes able to predict cardiovascular disease progression and mortality (14).…”
mentioning
confidence: 99%
“…A high cumulative physiological wear and tear, referred to allostatic load (AL) and considered a marker of chronic stress, has already been described in disabled children (14). AL is a preclinical marker of pathophysiological processes that can be considered a key mediator of adversity and negative health outcomes able to predict cardiovascular disease progression and mortality (14). More than 40% of the NI subjects showed high AL, significantly correlated with malnutrition (13) and potentially influencing outcome.…”
mentioning
confidence: 99%